Atmospheric particulate pollution on physiological function of athletes in high intensity training - Zhu, R. (Caribbean Journal of Science, 2019)
Atmospheric particulate matter pollution has a significant impact on the physiological function of athletes in high-intensity training. Long-term high-intensity training in polluted environment will lead to the decline of athletes' physical fitness. In order to alleviate the impact of atmospheric particulate matter pollution on athletes' physical fitness, the correlation statistical analysis and evaluation are carried out; the sources of atmospheric particulate matter pollution in training environment are analyzed to reveal the impact of atmospheric particulate matter pollution on athletes' physical fitness. Different levels of atmospheric particulate matter pollution affect the efficiency of athletes' physical fitness in different gradient, which leads to the decline of athletes' physical training level and affects athletes' physical fitness indicators. Through the prevention and control of atmospheric particulate matter pollution, scientific training plan is formulated to alleviate the impact of atmospheric particulate matter pollution on the physiological function of athletes in high-intensity training.